2016
DOI: 10.5999/aps.2016.43.6.491
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Vascular Endothelial Growth Factor (Bevacizumab) Therapy Reduces Hypertrophic Scar Formation in a Rabbit Ear Wounding Model

Abstract: BackgroundHypertrophic scarring is a pathological condition that occurs after trauma or surgery. Angiogenesis occurs more often with hypertrophic scarring than with normotrophic scarring. The regulation of angiogenesis is one of the key factors in hypertrophic scar management. Vascular endothelial growth factor (VEGF) is an essential factor in the angiogenetic response. This study investigated whether decreasing the level of VEGF is effective for treating hypertrophic scarring.MethodsTen 8-week-old female New … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 21 publications
2
22
0
Order By: Relevance
“…24,[55][56][57] Some studies demonstrate that the reduction in the hypertrophic scar is associated with a decrease in angiogenesis, and a few have directly explored the use of antiangiogenic therapies, including anti-VEGF and endostatin, to reduce scar formation in the rabbit model. [58][59][60] Together with the current study, then, a growing body of data supports the concept that robust angiogenesis spurs fibrosis in skin wounds, and that inhibition of angiogenesis, at least with the subgroup of agents that decreases VEGF activity, can reduce scar formation.…”
Section: Discussionsupporting
confidence: 75%
“…24,[55][56][57] Some studies demonstrate that the reduction in the hypertrophic scar is associated with a decrease in angiogenesis, and a few have directly explored the use of antiangiogenic therapies, including anti-VEGF and endostatin, to reduce scar formation in the rabbit model. [58][59][60] Together with the current study, then, a growing body of data supports the concept that robust angiogenesis spurs fibrosis in skin wounds, and that inhibition of angiogenesis, at least with the subgroup of agents that decreases VEGF activity, can reduce scar formation.…”
Section: Discussionsupporting
confidence: 75%
“…This effect associated with the expected drop in tissue VEGF level. 19 Similarly, Wang et al showed that when rabbits with nascent ear hypertrophic scars were injected topically with recombinant human endostatin, the scars had lower scar elevation index values, less connective tissue, fewer microvessels and fibroblasts, and smoother collagen fibers. These effects associated with lower VEGF levels in the scars.…”
Section: Huang and Ogawamentioning
confidence: 98%
“…Rabbit ear is a commonly used experimental model for vascular treatment. 14,15 However, the small vascular net seen between central artery and collecting marginal vein is actually arteriovenous communications, used physiologically for the animals' temperature control. 16 These vessels have high blood flow, which makes their sclerosis a challenge in some therapies.…”
Section: Discussionmentioning
confidence: 99%